2008
DOI: 10.1029/2007jc004212
|View full text |Cite
|
Sign up to set email alerts
|

Complex dielectric constant of sea foam at microwave frequencies

Abstract: [1] We present a systematic investigation of the applicability of a group of mixing rules for obtaining the dielectric constant (permittivity) of sea foam (whitecaps) at microwave frequencies, 1.4 to 37 GHz. By demonstrating that the foam scattering is weak at these frequencies, we justify our interest in basic mixing rules, which do not involve explicit scattering computation, namely, the Maxwell Garnett, Polder-Van Santen, Coherent potential, Looyenga, and Refractive models. The complex dielectric constant o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 62 publications
3
68
0
1
Order By: Relevance
“…The bubbles on the top level of the foam layer are polyhedral with lower water fractions, whereas the bubbles on the bottom of the foam layer tend to be small with higher water fractions and almost buried in seawater [5,6,9]. Fig.…”
Section: Physical Model Of Foam Layermentioning
confidence: 99%
See 1 more Smart Citation
“…The bubbles on the top level of the foam layer are polyhedral with lower water fractions, whereas the bubbles on the bottom of the foam layer tend to be small with higher water fractions and almost buried in seawater [5,6,9]. Fig.…”
Section: Physical Model Of Foam Layermentioning
confidence: 99%
“…Raizer [8] developed a composite microwave model for estimating the emissivity of sea foam, by incorporating the vertical profile of an effective permittivity, which was associated with air-water stratifications. Anguelova and Gaiser [9,10] determined the effective permittivity of sea foam layers by comparing five kinds of mixing rules based on the effective medium theory; the importance of multiple interactions between air-foam and foamseawater interfaces was noted in their studies. To achieve more robust applications of microwave remote sensing of an ocean surface, more comprehensive physical characterizations of microwave scattering and emission from a foam-covered ocean surface are required, such as the study of surface roughness driven by wind over the ocean surface, interactions of the foam layer with the sea surface, and their effects on the directional wave spectrum of short gravity and capillary waves [11].…”
Section: Introductionmentioning
confidence: 99%
“…Whitecaps in their decaying phase are thinner and dimmer and are referred to as residual whitecaps. Anguelova [24] gives an extended definition of the sea foam.…”
Section: Sea Foam As a Mediummentioning
confidence: 99%
“…To describe oceanic whitecaps under various conditions and in different lifetime stages, the full range of void fractions f a (from 0 to 1) needs to be considered [24]. It was shown that various functional forms could represent the shape of the void fraction profile in the foam depth [25].…”
Section: Sea Foam As a Mediummentioning
confidence: 99%
See 1 more Smart Citation